Anatomy and neural remodeling of the renal sympathetic nerve in a canine model and patients with hypertension. Issue 10 (October 2018) - Xiong, Bo; Li, Jianbo; Yao, Yuanqing; Qian, Jun; Rong, Shunkang; Zhang, Peng; Jiang, Rong; Yang, Gang; Zhu, Que; Jiang, Yonghong; Zhou, Qi; Liu, Dichuan; et al.
Abstract : Background: The role of renal sympathetic nerve (RSN) in hypertension should be better understood. We aimed to three-dimensionally reconstruct the renal nerves, and explore its anatomical and histochemical characteristics in hypertensive canine model and patients. Methods: Renal arteries with surrounding tissue were collected from canines and cadavers with or without hypertension. Serial renal artery hematoxylin–eosin sections were used for three-dimensional reconstruction, and morphological parameters were collected and analyzed. Results: In hypertensive canines, the mean renal nerve number was 26.71 ± 5.68 versus 19.84 ± 5.68 in controls ( P  = 0.02), and the middle renal nerve volume was 5.31 ± 2.13 versus 2.60 ± 1.00 μl in controls ( P  = 0.01). Renal tissue norepinephrine concentrations, tyrosine hydroxylase and substance P immunoreactivity in RSN, and growth-associated protein 43 immunoreactivity in renal ganglion were significantly increased in hypertensive canines. In humans, the renal nerve was evenly distributed along the renal artery in a network pattern. The renal ganglion volume was 72.75 ± 33.43 in hypertensive patients versus 37.04 ± 23.95 μl in controls ( P  = 0.029) and the mean neuronal size in renal ganglion was 1187.3 ± 219.9 μm 2 in patients versus 714.8 ± 142.7 μm 2 in controls ( P  = 0.002). Tyrosine hydroxylase immunoreactivity in the RSN was 0.153 ± 0.014 in patients versus 0.104 ± 0.019 in controls ( P  = 0.013). Growth-associated protein 43 immunoreactivity in the renal ganglion was 86 612.8 ± 14 642.0 in patients versus 33 469.8 ± 15 666.8 μm 2 /mm 2 in controls ( P  < 0.001). Conclusion: Our study suggests that RSN and renal ganglion histological remodeling occurs in individuals with hypertension and the distal segment or branches of renal artery might be a promising therapeutic target for RSN modulation therapy. Abstract : Supplemental Digital Content is available in the text